Clinical Study of khandakushmanda Avaleha And Patoladi kwatha on Amlapitta W.S.R. GERD (Acidity) - A Pilot Study - Chhimpa, Rakesh; Mothaliya, Khyati; Dadhich, Om Prakash (International Research Journal of Ayurveda & Yoga, 2021)
Amlapitta (Acidity) is a burning problem of today’s society. This has given rise to many other serious diseases. Now day there is a drastic change in life style of mankind in all aspects due to modernization and industrialization. So, to cope-up with speed, the human beings are adapting to junk food preparations and over work, exposing to stress and sedentary life style resulting into lack of exercises. Lakshanas(Symptoms) of Amlapitta (Acidity) like Amlodgara (sour eructation) Daha(burning sensation) are encountered by cardinal signs of GERD such as Gastro-esophageal reflux and gastritis. Usually, patients suffer with heart burning and the condition affects over a number of people widely now a days. The more the condition is novel and recently onset, the more it can treat without difficult. If it lasts with a long duration, more troublesome for treatment. Modern medicines are not having proper effect for gastric diseases. Ayurveda offers secure, low cost effective and fruitful management that affordable with all kind of people. Keeping this fact in mind these study is carried out.In this study total 15-15 patients were divided in to two groups by simple random method and administrated it on patients. After complete the trial appropriate statistics were applied. At the end we got very good result that is mentioned in whole paper.